Review of Urban Content in International Institutions’ Reports of 2022: Paving the Way Towards Sustainability and Resilience (Journal of human and social sciences, 2023)
In recent years, cities and urban areas have become the focus of international institutions, civil society organizations, and researchers in the field of urban development. This growing interest is mainly driven by three factors: first, the demographic shift revealed by global statistics showing that, since 2007, more than 50% of the world’s population lives in cities, marking an unprecedented change in settlement patterns. Second, the significant contribution of major urban areas to greenhouse gas emissions and solid waste, which have been linked to pollution and climate change. Third, the unsustainable patterns of urbanization that have led to major environmental, social, and economic challenges. In 2022, several international reports were published addressing development, economy, and climate change. These reports provided descriptions of prevailing living conditions, data analysis, and roadmaps for achieving sustainability. This paper reviews key insights from those reports concerning urban sustainability and resilience. The adopted methodology is based on three steps: selecting reports with explicit urban focus, analyzing their main components related to urban patterns, challenges, and future scenarios, and finally proposing measures and policies relevant to the local context. Keywords: Cities – Sustainability – Urban Resilience – Urban Planning
Keywords: Infrastructure; Urbanization; Sustainable Development; Green Cities; Circular Economy